PENGARUH CASH HOLDING DAN RETURN ON ASSET TERHADAP NILAI PERUSAHAAN DIMODERASI OLEH DEBT TO EQUITY RATIO - Salma, Syarifah; Hermuningsih, Sri; Hidayat, Riskin (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The aim of the study is to examine the influence of cash holding and return on assets on firm value with the debt to equity ratio as moderation. The data type is secondary. The population is health sector companies in the ISSI. The sampling technique used purposive sampling. The research data is financial reports published on the Indonesia Stock Exchange 2019-2023. Analysis using the PLS-SEM method evaluates the outer and inner models. Includes convergent validity, discriminant validity, and composite reliability, Cronbach's alpha for parameter blocks. Also, the R-square value for construct validity and the Standard Root Mean Residual value for model fit, then hypothesis testing. Data was processed with SmartPLS 4.0 software. This research shows that cash holding has no significant effect, return on assets has a significant positive effect, the debt to equity ratio is able to weaken the influence between cash holding and firm value, and the debt to equity ratio is able to strengthen the influence between return on assets and firm value. Keywords: Cash Holding, Return on Asset, Firm Value, Debt to Equity Ratio.